2012
DOI: 10.1021/jp308648u
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Librational Relaxation of H2O in Liquid Water

Abstract: The ultrafast librational (hindered rotational) relaxation of a rotationally excited H2O molecule in pure liquid water is investigated by means of classical nonequilibrium molecular dynamics simulations and a power and work analysis. This analysis allows the mechanism of the energy transfer from the excited H2O to its water neighbors, which occurs on a sub-100 fs time scale, to be followed in molecular detail, i.e., to determine which water molecules receive the energy and in which degrees of freedom. It is fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
67
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(78 citation statements)
references
References 39 publications
11
67
0
Order By: Relevance
“…Here we can draw a parallel with the results for pure rotational excitation in Ref. 53: there it was found that rotational transfer is extermely rapid, so that energy does not sit on any water molecule for long; in addition, rotational excitations of up to 15 kcal/mol did not produce any noticeable changes in mechanism (in terms of percentages of energy flowing into the different modes).…”
Section: Fluxes Into Hydration Shellssupporting
confidence: 73%
See 1 more Smart Citation
“…Here we can draw a parallel with the results for pure rotational excitation in Ref. 53: there it was found that rotational transfer is extermely rapid, so that energy does not sit on any water molecule for long; in addition, rotational excitations of up to 15 kcal/mol did not produce any noticeable changes in mechanism (in terms of percentages of energy flowing into the different modes).…”
Section: Fluxes Into Hydration Shellssupporting
confidence: 73%
“…This is an issue that will arise several times, although we attempt not to be repetitive. The energy flow from the produced rotationally excited central water molecule was characterized in detail as well 53 . It is less local in character than that directly from the bend to the first hydration shell: approximately 80 % of its rotational kinetic energy being transferred to water molecules in the first shell, with an even sharing by molecules accepting or donating hydrogen bonds.…”
Section: Fluxes Into Hydration Shellsmentioning
confidence: 99%
“…This indicates that the dipole motions are governed by the hydrogen bond dynamics in liquid water. In the previous simulations on liquid water 15,16,[36][37][38][39][40][41] , distinctly separated slow and fast molecular motions have been observed due to the hydrogen bond network.…”
Section: Introductionmentioning
confidence: 90%
“…Several previous reports have shown that this energy flow approach results in a clear-cut understanding of molecular mechanisms involved in rotational/librational and vibrational relaxation of neat liquid water. [14][15][16] (The rotations in liquid water are of course hindered rotations, i.e. librations; we will use both appellations).…”
Section: Introductionmentioning
confidence: 99%